Validation of agent-based models in economics and finance - Giorgio Fagiolo; Mattia Guerini; Francesco Lamperti; Alessio Moneta; Andrea Roventini (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2017)
Since the influential survey by Windrum et al. (2007), research on empirical validation of agent-based models in economics has made substantial advances, thanks to a constant flow of high-quality contributions. This Chapter attempts to take stock of such recent literature to offer an updated critical review of existing validation techniques. We sketch a simple theoretical framework that conceptualizes existing validation approaches, which we discuss along three different dimensions: (i) comparison between artificial and real-world data; (ii) calibration and estimation of model parameters; and (iii) parameter space exploration.
Keywords: C15; C52; C63; 330; agent based models; validation; calibration; sensitivity analysis; parameter space exploration